KARAKTERISASI TOKOH DALAM NOVEL SAMPAI JUMPA DI SURGA KARYA IPNU RINTO NOEGROHO - RAKOMOLE, DEWINTA N.; PANDEAN, MARIAM LIDIA MYTTY L.M.; KAROUW, STELLA S.M. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitled "Characterization of Figures in Sampai Jumpa di SurgaNovel". The focus of this research is on the characterization process Nurgiyantoro concept of based on figure character analysis in the novel of tettle review. They are character clasifications by Nurgiyantoro, they are: main character, supporting character, protagonist character and    antagonist character, simple character and complex character, static character and developed character, netral character and tipical character.  Method used in this research is descriptive. It described the characters based on the analysis. It can be shown that the main characters, Raiza, Amar, and Ulfa, are protagonist. Raiza is kind, humble, easy going, smart, wise and optimistic, Amar is humorous, wise, critical, and humble, and Ulfa is too sensitive, wise, and smart. Spporting characters who are protagonist are Hafiz, Pak Haji Salim, Mbak Gita, Mrs. Retno, Pak Udin, Mbak Hannah, Haikal, Firman, Sigit, Aldi, Ustadz Hanafi, Bu Ayu, Wisnu, Haris, Akbar, Madam, Ihsan , Ustazah Qianita, Mrs. Rohana, Ahri, Doctor Krisna, and Bi Nini. Those characters possessed kindness, optimistic, hard work, wise, critical, abd humble. The supporting antagonist character is Nyonya, she is egoistcs and proud.      Keywords: characters, novel, sampai jumpa di surga